UMA LENTE NO OLHAR DO ESTUDANTE COM AUTISMO: UMA POSSIBILIDADE DE ENSINAR E APRENDER SOBRE AS FLORES - Barreto, Bruna Bertoldo (2023)
This study is part of the Teaching and Learning of Science and Mathematics research line, of the Graduate Program in Science and Mathematics Teaching at Universidade Franciscana, and was conducted within the professional context, in which I work as a teacher, in a school for students with Autism Spectrum Disorder (ASD). In Special Education, little is said about the teaching-learning of specific contents of the different areas of knowledge in Elementary Education, and it is perceived that contents that involve reflection on natural phenomena and their transformations are treated superficially and in a simplified way. In addition, the lack of didactic resources and strategies for the teaching-learning of this theme is identified. In an analysis of different educational products already published, and considering the importance of the study of flowers and the use of images for the learning of students with ASD, the educational product Didactic sequence for the study of flowers, authored by from Pigatto et al. (2018), which was designed and thought for atypical students. From this, the problem of this research was defined: what are the potentialities of an educational product, which addresses the study of flowers through photography, in view of the teaching-learning of students with Autism Spectrum Disorder (ASD)? To address this problem, the objective of the work was delimited, that of investigating the potential of an educational product, which addresses the study of flowers through photography, in view of the teaching-learning of students with ASD. The research was characterized as a qualitative and exploratory approach, and was developed with five students from the Escola Municipal Especial de Ensino Fundamental Professor Luiz Francisco Lucena Borges, in Porto Alegre/RS, an institution that welcomes students, predominantly with Autism Spectrum Disorder and their comorbidities, from six to twenty-one years of age. For the elaboration of the didactic sequence adapted to the research participants, an interpretative analysis of the educational product Didactic sequence for the study of flowers was carried out. Subsequently, the didactic sequence designed for students with ASD was applied at school, and the data obtained were discussed with the school's teachers, through a conversation circle, in order to verify the perception of the behavior and attitudes of their students, after the application of activities. It is concluded that the adapted didactic sequence has the potential to be replicated and used from kindergarten to the 3rd year of elementary school, since the students showed curiosity and satisfaction in handling the cell phone camera and discovering the different flowers in the courtyard of the school. According to the National Common Curricular Base, it was possible to approach objects of knowledge of the unit Life and Evolution, especially on the characteristics of flowers such as size, colors and shapes. This didactic sequence constituted an educational product entitled Discovering flowers with photography: a proposal in science teaching for students with autism, which will be made available on the PPGECIMAT and eduCAPES pages.